Different approaches to the protection and enhancement of underwater archaeological sites: Acquirements and Aspirations - Pari Kalamara (Annals of Marine Science - Peertechz Publications, 2022)
This paper presents aspects of underwater cultural heritage management in Greece, focusing mainly on accessibility to the diving community and the general public. More specifically, it discusses different approaches to the protection and enhancement of Underwater Archaeological Sites, already put into practice over the last years (2018-2021) by the Ephorate of Underwater Antiquities, the public service of the Hellenic Ministry of Culture and Sports responsible for the management of underwater heritage. Moreover, it analyses the aspirations for the future, as these took shape already at the beginning of 2021. Lately, cultural management has turned into a fast-growing sector with multilevel developmental prospects. In order to tap into the underwater cultural heritage potential, we must always take into consideration the identity and special characteristics of each underwater site as well as the different possibilities of access - physical or virtual - that are rapidly changing because of new technological achievements. All these parameters affect significantly decision making and the undertaking of relevant initiatives. Examples of the pilot implementation of the opening of underwater archaeological/cultural sites to the public will be presented. Through them, preliminary conclusions concerning the efficacy of the selected managerial approaches can be drawn, while at the same time domains where more should be done will be highlighted.